Pola segregasi karakter agronomi tanaman kacang panjang (Vigna unguiculate (l.) spp. sesquipedalus) generasi F2 hasil persilangan varietas Super Putih x Fagiola IPB - Adinda Rachmawati; Syaiful Anwar; Karno Karno (Department of Agriculture, Animal and Agricultural Sciences, Diponegoro University, Semara, 2020)
ABSTRACTThe purpose of this research was to analyze the segregation pattern of agronomic characters in the second generation of long beans produced by crossing Super Putih x Fagiola IPB varieties. The research was using a single plant design by planting 120 F2 generation plants and 10 old plants were plated without repetition. The parameters observed included plant height, leaf number, branch number, flowering age, long young pod, number of old pods, seed number, weight of 100 seeds, pods color, and seeds color. The data were analyzed by distribution suitability test and chi-square test. The result showed that the abnormal distributed characters were plant height and seed number with selection could be done in early generation because its have high inheritance. Plant height segregation patterns was referring to Mendelian ratio 9:7 with the action of two duplicate recessive epistatic genes, seed number patterns was referring to Mendelian ratio 12:3:1 with the action of the dominant epistatic gene, the color of pods and the color of seeds patterns was referring to Mendelian ratio 13:3 with the action of two recessive dominant epistatic genes. Key words: long beans, agronomic characters, segregation patternsABSTRAKPenelitian ini bertujuan untukmenganalisis pola segregasi karakter agronomi generasi F2 kacang panjang hasil persilangan varietas Super Putih x Fagiola IPB. Penelitian disusun dengan rancangan single plant dengan menanam sebanyak 120 tanaman generasi F2 dan tetua sebanyak 10 tanaman yang ditanam tanpa ulangan. Parameter yang diamati yaitu tinggi tanaman, jumlah daun, jumlah cabang, umur berbunga, panjang polong muda, jumlah polong tua, jumlah biji per tanaman, bobot 100 biji, warna polong, dan warna biji. Data dianalisis dengan uji kesesuaian distribusi dan uji khi-kuadrat. Hasil penelitian menunjukkan bahwa karakter yang tidak berdistribusi normal adalah tinggi tanaman dan jumlah biji, sehingga seleksi dapat dilakukan pada generasi awal, karena memiliki daya waris yang tinggi. Pola segregasi tinggi tanaman mengikuti nisbah Mendel 9:7 dengan aksi dua gen epistatis resesif duplikat, jumlah biji mengikuti nisbah Mendel 12:3:1 dengan aksi dua gen epistatis dominan, sedangkan warna polong dan biji mengikuti nisbah Mendel 13:3 dengan aksi dua gen epistatis dominan resesif.Kata kunci : kacang panjang, karakter agronomi, pola segregasi